PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK PADA MATERI IPAS PERUBAHAN ENERGI SISWA KELAS IV SDN TAROKAN 3 KEDIRI - Cantika Sabrinatasari; Wahid Ibnu Zaman; Muhamad Basori (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In fourth-grade science instruction at Tarokan 3 Elementary School, teachers do not use instructional media and still rely on teacher and student textbooks as teaching aids. This makes students less active in learning about energy transformations. Based on observations and interviews, only 15 of 40 students achieved the minimum grade point average (KKTP) (75). This study aims to determine the effectiveness of using the "Big Book" instructional media in increasing students' interest in reading. This study used the Research and Development (R&D) method with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects were 40 fourth-grade students, with data collected through observation, interviews, and tests. The instructional media were tested on both a limited and a broad scale. The results of the limited trial showed a completion rate of 100%, and the broad trial showed a completion rate of 100%. These results indicate that the "Big Book" learning media is very effective in improving student learning outcomes, exceeding the KKTP score, and can be used without the need for improvement.